Ferritinophagy and ferroptosis in the management of metabolic diseases - Ajoolabady, Amir; Aslkhodapasandhokmabad, Hamid; Libby, Peter; Tuomilehto, Jaakko; Lip, Gregory Y.H.; Penninger, Josef M.; Richardson, Des R.; Tang, Daolin; Zhou, Hao; Wang, Shuyi; Klionsky, Daniel J.; Kroemer, Guido; et al. (TRENDS IN ENDOCRINOLOGY AND METABOLISM, 2021)
Ferroptosis is a form of regulated cell death modality associated with disturbed iron-homeostasis and unrestricted lipid peroxidation. Ample evidence has depicted an essential role for ferroptosis as either the cause or consequence for human diseases, denoting the likely therapeutic promises for targeting ferroptosis in the preservation of human health. Ferritinophagy, a selective form of autophagy, contributes to the initiation of ferroptosis through degradation of ferritin, which triggers labile iron overload (IO), lipid peroxidation, membrane damage, and cell death. In this review, we will delineate the role of ferritinophagy in ferroptosis, and its underlying regulatory mechanisms, to unveil the therapeutic value of ferritinophagy as a target in the combat of ferroptosis to manage metabolic diseases. Ferroptosis is a form of regulated cell death that is driven by iron overload and lipid peroxidation.Ferroptosis contributes to the onset or progression of various metabolic diseases.Ferritinophagy is a selective type of autophagy, which induces ferroptosis by degrading ferritin and inducing iron overload.Ferritinophagy inhibition may ameliorate ferroptosis and ease the management of metabolic diseases.